Profil Kesehatan Pelajar Sekolah Dasar di Kecamatan Bambanglipuro, Kabupaten Bantul, DIY - I Gusti Bagus Suryanegara; Mitra Andini Sigilipoe; Daniel Chriswinanto Adityo Nugroho; The Maria Meiwati Widagdo (Universitas Ciputra Surabaya, 2022)
The World Health Organization (WHO) reported the prevalence of underweight in children in the world was around 14.3% with the number of underweight children thinness as many as 95.2 million in 2015. One of the main goals of national development is to improve the quality of human resources. School-age children need good nutrition to support learning activities at school. This study aims to determine the health profile of students in grades one through six elementary schools in Bambanglipuro District, Bantul Regency, Special Region of Yogyakarta. This research is a descriptive study using secondary data. The inclusion criteria were elementary school students in Bambanglipuro District from grade one to grade six. The exclusion criteria were students who did not have complete health records. All data was analyzed by Microsoft excel. The total number of respondents in this study was 2,562 people. From the results of the study, the percentage of BMI in the normal category for male students was 52% while the female was 48%. The number of students with a BMI in the obese category was found to be a total of 12 (0.5%) students, divided into 5 male students and 7 female students. In the